A Review of Goods and Services Tax (GST): Impact on Indian Stock exchanges and various stock Sectors. - Dr Manoj Sain**, Mr Priyanshu Sharma*, (International Journal of Scientific Research and Management (IJSRM), 2017)
Till such time as GST fears subside, it is good to look at stocks outside the Sensex. For those with strong nerves, it would make sense to play the contrarian game, ahead of the RBI’s credit policy change in August. Analysts believe the short-term impact of GST could be neutral to negative and positive, though this huge tax overhaul is expected to give further direction to the economy and markets. There are expectations that GST will boost India’s GDP growth by 150-200 basis points in the coming years. However, the rollout may impact first quarter earnings of India Inc, as companies will take some time to align their production processes with the new framework, adjust to the input tax credit system and get a handle on their working capital requirements. Input credit allows a seller to reduce the tax burden being paid by claiming offset for the taxes already paid on inputs.